Influences of Gender, Age and Income Differences on Consumers’ Purchase Items - Rahman, Matiur; Turpin, Lonnie; Al Emran, Md. (STIE Malangkucecwara, 2024)
This paper studies whether gender, age and income differences matter for in-store purchases of selected non-durable and durable consumer goods in the Southwest region of the State of Louisiana. Primary data are collected by face-to-face interviewing of randomly selected adult population within the age groups 15 years to 64 years, and above. Using the collected primary data for categorical variables, -tests are implemented for six separate null hypotheses of statistical independence between/among variables of interest. The results reveal that only gender difference matters the most for in-store purchases of both non-durable and durable goods in the region. Age and income differences to have no significant influences on such purchases. As the findings suggest, the regional in-store retailers should focus more on female shoppers to promote sales of non-durable goods. At the same time, they should focus more on male shoppers for promotion of sales of durable goods in the region. Due cautions are in order for any kind of generalization of the findings of this study, given the extreme regional characteristics of the primary data. Key Words: Retail Sales, In-Store, Non-Durable Goods, Durable Goods, Shoppers, Age, Gender, Income JEL Classifications: D10, D11, D12